Executive function and personality: The moderating role of athletic expertise. (15th July 2020) - Vaughan, Robert S.; Edwards, Elizabeth J.
Abstract: The relationship between personality, executive function (EF) and athletic expertise has implications for researchers and sports psychologists, alike. The current study examined the relationship between the five-factor model of personality, the lower-order model of EF, and athletic expertise. A sample of 367 participants (57% male; M age = 21.9) with a range of athletic expertise (super-elite = 64; elite = 65; amateur = 75, novice = 74, and non-athlete = 89) completed a personality inventory and computerised battery of EF. Individuals with more athletic expertise reported higher extroversion, openness, and conscientiousness and better EF scores, whereas those with less expertise reported higher neuroticism and agreeableness. Results of structural equation modelling indicated that EF was largely positively related to openness and conscientiousness, negatively related to neuroticism, bi-directionally related to extroversion, and unrelated to agreeableness. Additionally, athletic expertise moderated the association between personality and EF. These findings untangle the relationship between athletes' personality and EF and have theoretical and practical implications for sports performance.